(untitled) (Baghdad Science Journal, 2018)
The present study deals with the morphological and histological aspects of the forebrain(Cerebrum) in the Columba livia domestica (Gmelin, 1789) to identify the histoarchitecture of its layers. This bird’ has a large head found as perpendicular to the longitudinal axis. The morphological results reveal that for brain (Cerebrum) pear shaped, its outer surface is smooth without folds or deep grooves. Cerebrum is made up of two regions, the Pallium and the Subpallium. The Cerebral cortex includes four layers of hyperpallium (Wulst) , Dorsolateral corticoid area (CDL), Hippocampus, Piriform cortex. The internal cortex of cerebrum consists of Dorsal Ventricle ridge which includes the mesopallium, nidopallium, and archospallium. All these regions includes Pyramidal cells, which have different sizes and densities, as well as many other neurons and Neuralgial. The Subpallium is divided to Striatum which is consisted of nerve fibers of nerve cells and the Palldium, which is the deepest part of the brain with light- color.